Atmospheric implications of aminomethylphosphonic acid promoted binary nucleation of water molecules - Ayiseh Frederick Tandong; Olivier Holtomo; David Afungchui (Chemical Thermodynamics and Thermal Analysis)
Aminomethylphosphonic acid (AMPA) is the main metabolite of glyphosate and phosphonate, the major constituents of herbicides and insecticides used nowadays in modern agriculture and treatment of environmental refuge and sewage. Through these activities, AMPA is released into the atmosphere which can result in water molecule adsorption around AMPA. The DFT method through the APF-D/6–31++G(d,p) was used throughout the work to cluster one to ten water molecules around AMPA and to find their concentrations in atmosphere along with climate forcing. It comes to light that, the binding energies of the complexes AMPA(H2O)n = 1–10 increase upon addition of H2O. The binding energy (ΔE) per H2O is approximatively -55.7 kJ/mol for n = 1 – 5 and -52.7 kJ/mol for n = 6 – 10. Likewise, the Gibbs free energy per H2O averages within the same ranges at -19.0 and -13.5 kJ/mol, respectively. Thus, AMPA easily forms clusters with water molecules in an exothermic reaction. This happens with high cluster concentrations and high evaporation rate constant. The concentrations, [AMPA(H2O)n], show that AMPA forms more complexes with water at higher relative humidity (saturated air) than lower relative humidity (moderate or dry air). However, the significant drop in the concentrations at n > 5, shows that the stability of the complexes reduces with cluster size. The evaporation rates of a single water evaporation pathway of AMPA(H2O)n are large enough thereby showing that binary clusters AMPA – water easily evaporate in the atmosphere. The presence of clusters, AMPA(H2O)n, in the atmosphere can contribute greatly to the atmospheric puzzles of global warming and climate change. This is supported by the estimates of radiative forcing efficiencies of AMPA(H2O)n.